Metagenomic evidence clarifies the texture-dependent cascading effects of organic degradation on soil hypoxia and N2O emission - Hu, Jialin; Cyle, K. Taylor; Yuan, Wenqiao; Shi, Wei (Frontiers in Microbiology, 2025)
IntroductionSoil pore-scale aeration is a crucial yet often overlooked factor influencing the effectiveness of nitrous oxide (N2O) emission mitigation strategies. Our previous work revealed a hundred-fold variation in N2O emissions among soils under apparently aerobic conditions and texture-dependent mitigation effects of biochar–manure co-compost (BM) compared to manure compost (M).MethodsWe analyzed soils of three textures—clay loam (CL), silt loam (SL), and sand (SA)—amended with BM or M. Metagenomic sequencing was used to profile microbial community composition and functional genes, with a focus on aeration-sensitive taxa and pathways.ResultsWe demonstrate that these changes of N2O emissions are aligned with variations in aeration-sensitive microbes and genes. SA, with the highest N2O emissions, was most abundant in obligate and facultative anaerobes and denitrification-related genes, while CL, with the lowest emissions, had more genes related to fermentation and dissimilatory nitrate reduction. Compared to M, BM in CL favored genes for microbial processes requiring a more reducing environment, likely because biochar-induced finer pores, exacerbating oxygen diffusion limitations. This severe oxygen restriction in CL after BM addition was substantiated by greater reductions in CO2 efflux and C-cycling genes than in the other soils.DiscussionOur findings suggest that hypoxic pore abundance and the severity of pore anaerobiosis imparted by degradation of organic amendments varied with soil texture and are the overriding factors of soil greenhouse gas (GHG) emissions. Metagenomic traits provide a sensitive tool for detecting pore-scale environmental shifts, improving our mechanistic understanding of soil-dependent GHG emissions following organic amendments.